The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1590/fst.119522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical properties of three types of bamboo shoot powders

Abstract: Powders were prepared from fresh Phyllostachys pubescens bamboo shoots (P. pubescens), Dendrocalamopsis oldhami bamboo shoots (D.oldhami) and Dendrocalamus latiflorus bamboo shoots (D.latiflorus), and their physical, chemical, adsorption and powder properties were determined. All three of these powders were high in dietary fiber and protein, with P. pubescens powder containing the highest concentration of dietary fiber (50.34 ± 0.65 g•100 g -1 ). The water holding, oil holding, and swelling capacities of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…As seen in Figure 4, during the whole storage period, the total content of the CK group fluctuated more, and the total content of the KM and SC groups fluctuated less. The AV and TBARS values of the sauce meat without added yeast were significantly higher than those of the sauce meat with added yeast, which was consistent with the changes in the moisture content of sauce meat in this experiment and the results of Zhang et al [1]. It can be noted that the AV value of the SC group was lower than that of the other two groups and was more stable during the storage period (Figure 4a), which indicated that S. cerevisiae had a certain antioxidant effect during the storage process of sauce meat, and it could also prevent the excessive oxidation of food products from producing an undesirable odor [48,53].…”
Section: Changes In Av Tbars and Pov Valuessupporting
confidence: 91%
See 1 more Smart Citation
“…As seen in Figure 4, during the whole storage period, the total content of the CK group fluctuated more, and the total content of the KM and SC groups fluctuated less. The AV and TBARS values of the sauce meat without added yeast were significantly higher than those of the sauce meat with added yeast, which was consistent with the changes in the moisture content of sauce meat in this experiment and the results of Zhang et al [1]. It can be noted that the AV value of the SC group was lower than that of the other two groups and was more stable during the storage period (Figure 4a), which indicated that S. cerevisiae had a certain antioxidant effect during the storage process of sauce meat, and it could also prevent the excessive oxidation of food products from producing an undesirable odor [48,53].…”
Section: Changes In Av Tbars and Pov Valuessupporting
confidence: 91%
“…Determination by the colorimetric method of ninhydrin concerning Zhang et al [1]. Scale curve equation: y = 0.0096x − 0.0145 where x is amino acid content (µg/mL) and y is absorbance (nm).…”
Section: Determination Of Free Amino Acid Contentmentioning
confidence: 99%